1976
DOI: 10.3181/00379727-151-39281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on the Luteinizing Hormone Release Induced by Clomiphene and Luteinizing Hormone-Releasing Hormone

Abstract: Much experimental evidence indicates that the pineal gland is involved in the regulation of reproductive function (1). This effect appears to be mediated, at least partially, by melatonin (2). It is well known that melatonin has a definite inhibitory influence on reproductive function (3,4). For instance, it has been demonstrated that the injection of melatonin into the third ventricle is followed by a decrease in the luteinizing hormone (LH) and follicle-stimulating hormone (FSH) plasmatic concentrations (4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…One criticism of this study is that the half life of melatonin is only 11 min (17) and these effects were seen 3 h later. Also, in contrast to the above study subcutaneous injections of melatonin for 6 days into rats did not prevent the pituitary response to LHRH (18). In addition, Kamberi et al (19) have reported that infusion of melatonin into hypophysial portal vessels of rats did not effect the level of LH in the plasma.…”
Section: Experimental and Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…One criticism of this study is that the half life of melatonin is only 11 min (17) and these effects were seen 3 h later. Also, in contrast to the above study subcutaneous injections of melatonin for 6 days into rats did not prevent the pituitary response to LHRH (18). In addition, Kamberi et al (19) have reported that infusion of melatonin into hypophysial portal vessels of rats did not effect the level of LH in the plasma.…”
Section: Experimental and Discussionmentioning
confidence: 55%
“…In addition, Kamberi et al (19) have reported that infusion of melatonin into hypophysial portal vessels of rats did not effect the level of LH in the plasma. One possible explanation for the negative findings of the infusion (19) and subcutaneous injection studies (18) was the low level of basal LH secretion in these studies which makes an inhibitory effect difficult to discern. The present investigation demonstrates that melatonin does have a direct effect on at least one enzyme system in the anterior pituitary.…”
Section: Experimental and Discussionmentioning
confidence: 91%
“…We have no adequate explanation of this finding, but it could be considered that around 20-to 26-day-old rats take place important events related to the hypothalamic control of go nadotropin secretion (the maturation of the positive feed back of ovarian steroids, for instance), that are probably connected with modifications in the effect of the different neurotransmitters on these pituitary hormones. In this re spect, it is interesting to note that changes in the effect of melatonin on LH-RH in prepubertal and adult rats has been described and it has been proposed that this modifica tion is involved in the maturation of the reproductive sys tem [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, the gland's predominant hormone, has been primarily designated for this effect [24,25,28,32]. In the male rat melatonin has been found to decrease the secretion ofgonadotropins [6,13,17,21] and to modify the synthesis [22], metabolism [7,14], and activity [1,4] of gonadal androgens.…”
Section: Introductionmentioning
confidence: 99%